PENYULUHAN INFORMASI OBAT SKABIES DI PUSKESMAS BATULICIN - Nur Mahdi; Rahmayani Maghfirah; Fatmawati (Jurnal Bakti untuk Negeri, 2023)
Scabies is the third of the twelve most common skin diseases in Indonesia. This disease often occurs in people or groups with inadequate hygiene. The most common symptom is itching, which gets worse at night. This activity aims to increase public knowledge regarding the disease, prevention, and provision of information on scabies drugs by distributing leaflets as drug information media related to scabies education along with information on the use of scabies drugs. From the results of the pretest, the average percentage that answered well was 20%, and after the presentation showed an increase to 90%. This shows that there has been an increase in improvement from before, and the public well can understand the material presented.